Effect of thickness on the electrical and optical properties of epitaxial (La0.07Ba0.93)SnO3 thin films. (August 2016) - Liu, Qinzhuang; Jin, Feng; Dai, Jianming; Li, Bing; Geng, Lei; Liu, Jianjun
Abstract: Transparent conductive oxide (La0.07 Ba0.93 )SnO3 (LBSO) thin films with thickness ranged from 220 nm to 11 nm were epitaxially grown on MgO substrate by pulsed laser deposition. The effect of thickness on the structural, transport, and optical properties of LBSO thin films was investigated in detail. With the film thickness decreasing, x-ray diffraction characterizations show that the LBSO (002) diffraction peak has no obvious shift, but the values of the full width at half maximum increase gradually from 0.608° to 1.136° due to the deterioration of crystalline quality of LBSO films. Atomic force microcopy reveals that the root-mean-square surface roughness of LBSO films decreases from 3.93 to 0.268 nm with film thickness decreasing. The lowest resistivity value of 1.181 × 10 −4  Ωcm at room temperature was observed in 220 nm thick films, with the highest carrier mobility of 41.06 cm 2  V −1  s −1 and carrier concentration of 8.377 × 10 20  cm −3 . Furthermore, the resistivity increases gradually with the decrease of LBSO film thickness. Temperature dependent resistivity measurements indicate that the metal-semiconductor transition temperature of LBSO thin film changes regularly with the film thickness. The optical band gap of LBSO thin film decreases from 4.58 to 3.55 eV with decreasing the thickness, which was explained by the Burstein-Moss effect. Graphical abstract: Highlights: Transparent and conductive (La0.07 Ba0.93 )SnO3 epitaxial films were grown on MgO substrates with different thickness. (La0.07 Ba0.93 )SnO3 film thicknesses were determined precisely using x-ray reflectivity. Room-temperature resistivity of 1.181 × 10 −4  Ωcm was observed in 220 nm thick films. Optical band gap decreases from 4.58 to 3.55 eV with the film thickness decreasing.